Despotic Leadership in Healthcare: A Pathway to Psychological Distress and Reduced Performance - Zoha Khalid; Dr. Samina Qasim (Al-Qanṭara, 2025)
This paper builds on the equity theory and conservation of resources theory to propose a model that explores how despotic leadership affects psychological distress and feelings of unfair treatment among healthcare employees. The authors hypothesized that interactional injustice plays an mediating role and examined whether the relationship between despotic leadership and interactional injustice is moderated by victim sensitivity. This research study is a quantitative cross-sectional study conducted among healthcare pharmacists, with a sample size of 310, based on purposive sampling with a deductive approach. Structural equation modeling was deployed to test the hypotheses. This research indicates that despotic leadership significantly impacts psychological distress and victim sensitivity also significantly moderates the despotic leadership and interactional injustice. This study suggests that organizations should focus on preventing employee exploitation, promoting fair treatment, and supporting those who are more sensitive to being treated unfairly. It also suggests that organizations should address abusive leadership by implementing behavioral training. Because it is the first of its kind to examine the effect of despotic leadership on pharmacist employees and the intervening role of interactional injustice, this study is exceptional. The application of equity theory and COR theory to the pharmaceutical sector has not been widely explored.